Genetic engineering: a promising tool to engender physiological, biochemical, and molecular stress resilience in green microalgae - Guihéneuf, Freddy; Khan, Asif; Tran, Lam-Son Phan (Frontiers in Functional Plant Ecology, 2016)
As we march into the 21st century, the prevailing scenario of depleting energy resources, global warming and ever increasing issues of human health and food security will quadruple. In this context, genetic and metabolic engineering of green microalgae complete the quest toward a continuum of environmentally clean fuel and food production. Evolutionarily related, but unlike land plants, microalgae need nominal land or water, and are best described as unicellular autotrophs using light energy to fix atmospheric carbon dioxide (CO2) into algal biomass, mitigating fossil CO2 pollution in the process. Remarkably, a feature innate to most microalgae is synthesis and accumulation of lipids (60-65% of dry weight), carbohydrates and secondary metabolites like pigments and vitamins, especially when grown under abiotic stress conditions. Particularly fruitful, such an application of abiotic stress factors such as nitrogen starvation, salinity, heat shock, etc., can be used in a biorefinery concept for production of multiple valuable products. The focus of this mini-review underlies metabolic reorientation practices and tolerance mechanisms as applied to green microalgae under specific stress stimuli for a sustainable pollution-free future. Moreover, we entail current progress on genetic engineering as a promising tool to grasp adaptive processes for improving strains with potential biotechnological interests.